2004
DOI: 10.1248/bpb.27.203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors to Decrease Plasma Concentration of an HIV Protease Inhibitor, Saquinavir in Ethanol-Treated Rats

Abstract: The mid-1990s, HIV protease inhibitors (PIs) have been largely responsible for recent successful results in the treatment of HIV infected patients.1) A combination use of two kinds of reverse transcriptase inhibitors and an HIV protease inhibitor, highly active anti-retrovial therapy (HAART), has been found to be a better therapy than either drug alone in reducing HIV RNA levels and increasing CD4 cell counts. 2)On the other hand, a systematic review about alcohol use and HIV pharmacotherapy by Kresina et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Nonetheless, this is an important finding in context with the report that alcohol is known to increase the toxicity and reduce the efficacy of HAART in HIV-1-infected individuals [26,28,86-88]. More specifically, the studies from Flexner and colleagues [88] and Shibata and colleagues [89,90] have shown that alcohol can increase the metabolism and decrease the bioavailability of PI and NNRTI, resulting in decreased efficacy. The presence of multiple PI and/or NNRTI in HAART regimen, in which PI also act as CYP3A4 inhibitors, make alcohol–CYP3A4–PI interactions complex.…”
Section: Role Of Cyp3a4 In Alcohol–haart Interaction and Its Implimentioning
confidence: 57%
See 1 more Smart Citation
“…Nonetheless, this is an important finding in context with the report that alcohol is known to increase the toxicity and reduce the efficacy of HAART in HIV-1-infected individuals [26,28,86-88]. More specifically, the studies from Flexner and colleagues [88] and Shibata and colleagues [89,90] have shown that alcohol can increase the metabolism and decrease the bioavailability of PI and NNRTI, resulting in decreased efficacy. The presence of multiple PI and/or NNRTI in HAART regimen, in which PI also act as CYP3A4 inhibitors, make alcohol–CYP3A4–PI interactions complex.…”
Section: Role Of Cyp3a4 In Alcohol–haart Interaction and Its Implimentioning
confidence: 57%
“…The PIs used in the HAART regimen are expected to interact with alcohol thereby altering their metabolism and antiviral activity, especially in HIV-infected monocytes/macrophages [82,87,89,90]. Thus, HIV-infected individuals who consume alcohol and take PIs are not only affected by decreased drug efficacy, but are also at high risk for deleterious alcohol–PI interactions leading to drug toxicity.…”
Section: Expert Opinionmentioning
confidence: 99%
“…We previously reported that pretreatment of the jejunal loop with 25 mM KCZ or 10 mM CsA did not alter CYP3A or Pgp function in the liver. 23) Yasuda et al reported that KCZ inhibited human CYP3A4 metabolism with a K i of approximately 0.02 to 5 mM (0.01-2.7 mg/ml) and increased Pgp-mediated cellular accumulation of substrates with a K i ranging from 3 to 25 mM (1.5-13.5 mg/ml). 24) In addition, Augustijns et al reported that the Pgp function was inhibited in the presence of CsA ranging from 5 to 10 mM in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] The fluorescent dye Rho123 has been extensively used as an index of Pgp-mediated transport in rodents and tissue cultured models. 8,[14][15][16][17][18] Several transporters other than expressed in the rat intestinal tract, for example, multridrug resistance associated protein (MRP), organic cation transporters (OCTs) and breast cancer resistance protein (BCRP). Dogan et al 23) studied the relationship between MRP1 expression and transport of 3 fluorescent dyes calcein acetoxymethyl ester (calcein-AM), carboxyfluorecein diacetate (CFDA) and Rho123 in combination with the MRP1 modulators cyclosporine A, probenecid and MK571, using 11 cell lines with different levels of MRP1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The total body clearance of Rho123 (CL tot ) was calculated by D/AUC 0-∞ , where D represents the intravenous dose of Rho123. According to our previous reports, 16,18) the excretion clearances of Rho123 from the systemic circulation to the intestinal lumen (CL ex,int ), bile duct (CL ex,bile ) and urine (CL ex,urine ) after intravenous administration was calculated by dividing the average of the total amount of Rho123 excreted into the intestinal lumen, bile duct or urine by the average of AUC last .…”
Section: Assay Methodsmentioning
confidence: 99%